2019
DOI: 10.1002/hipo.23127
|View full text |Cite|
|
Sign up to set email alerts
|

Hippocampal BDNF regulates a shift from flexible, goal‐directed to habit memory system function following cocaine abstinence

Abstract: The transition from recreational drug use to addiction involves pathological learning processes that support a persistent shift from flexible, goal‐directed to habit behavioral control. Here, we examined the molecular mechanisms supporting altered function in hippocampal (HPC) and dorsolateral striatum (DLS) memory systems following abstinence from repeated cocaine. After 3 weeks of cocaine abstinence (experimenter‐ or self‐administered), we tested new behavioral learning in male rats using a dual‐solution maz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 113 publications
(182 reference statements)
1
5
0
Order By: Relevance
“…In the present study, both cocaine and microglia depletion reduced the levels of BDNF in the hippocampus. In agreement with our results, it has been shown that repeated administration of cocaine leads to a reduction of this neurotrophic factor in the hippocampus 78 , 79 . Although microglia may not represent the main source of BDNF in the brain, the release of this neurotrophin by these cells seems to be important in physiological and pathological conditions 80 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, both cocaine and microglia depletion reduced the levels of BDNF in the hippocampus. In agreement with our results, it has been shown that repeated administration of cocaine leads to a reduction of this neurotrophic factor in the hippocampus 78 , 79 . Although microglia may not represent the main source of BDNF in the brain, the release of this neurotrophin by these cells seems to be important in physiological and pathological conditions 80 .…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, intrahippocampal infusion of BDNF facilitates strategy shifting by minimizing response perseveration to the previously acquired strategy [ 36 ]. Additional evidence has shown that the flexible memory system was associated with up-regulation of BDNF expression and transcriptionally permissive histone acetylation in the HPC [ 37 ]. Moreover, compelling evidence showed BDNF-mediated neural excitability verifying successful learning [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to what was previously reported (Hofer et al, 1990), we did not detect BDNF-positive neurons in the striatum. Interestingly, although basal BDNF levels in the rodent striatum are negligible, a robust increase in BDNF message is detected in response to behaviors such as voluntary alcohol intake (McGough et al, 2004;Jeanblanc et al, 2009), and cocaine (Liu et al, 2006;Harvey et al, 2019), as well as in response to exercise (Marais et al, 2009). Reconciling these potentially conflicting observations merits further investigation.…”
Section: Characterization Of Corticostriatal Bdnf Neuronsmentioning
confidence: 99%